1990
DOI: 10.1111/j.1467-954x.1990.tb00920.x
|View full text |Cite
|
Sign up to set email alerts
|

To Risk or Not to Risk? Uses and Limitations of Mary Douglas on Risk-Acceptability for Understanding Health and Safety at Work and Road Accidents

Abstract: The recent Greening of politics in the West has encouraged rapid development of research into both environmental hazards and risk perceptions among the public. There are also longstanding traditions of research into behaviour under risk in such disparate fields as superpower relations (Allison 1971), inter-country commercial transactions, the economics of uncertainty, and the study of natural disasters (Torry 1979). Relatively few sociologists or social anthropologists have contributed. A major exception is Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…In the mobility version individuals are assumed to adopt different cultural biases as they move between institutions. Similarly, Bellaby (1990) has suggested that 'Douglas was unable to explain why individuals might move from one risk culture to another,' presenting serious implications for developing methods to test the theory. It has also been suggested that Douglas was not clear about whether cultural groups should be classified in terms of group and grid on the basis of their own (emic) concepts or those of the analyst (etic) (Wight 1999).…”
Section: Insert Figure One About Herementioning
confidence: 99%
See 4 more Smart Citations
“…In the mobility version individuals are assumed to adopt different cultural biases as they move between institutions. Similarly, Bellaby (1990) has suggested that 'Douglas was unable to explain why individuals might move from one risk culture to another,' presenting serious implications for developing methods to test the theory. It has also been suggested that Douglas was not clear about whether cultural groups should be classified in terms of group and grid on the basis of their own (emic) concepts or those of the analyst (etic) (Wight 1999).…”
Section: Insert Figure One About Herementioning
confidence: 99%
“…Douglas' cultural theory is useful in that it demonstrates that judgements made about danger, pollution, and threat are dependent more upon a wider social context than individual design (Tansey and O'Riordan 1999). The emphasis is not only on how individuals think but also on how groups and institutions think and set boundaries (Bellaby 1990). Certain dangers that make sense to a particular culture, and are therefore selected for attention as a 'risk,' are based on that culture's shared values and concerns (Douglas 1992).…”
Section: Insert Figure One About Herementioning
confidence: 99%
See 3 more Smart Citations